Herpetología patagónica : I. Liolaemus del grupo Magellanicus: características taxonómicas y genéticas - Cei, José Miguel Alfredo María (1971)
The patagonian iguanids Liolaemus magellanicus and L. lineomaculatus are comparatively described. Both species occupy the southermost ecological niches and are sympatric in most of their respective areas. Biological and ecological characteristics of both entities are also described.